High-density genetic linkage mapping reveals low stability of QTLs across environments for economic traits in Eucalyptus - Zhu, Xianliang; Weng, Qijie; Bush, David; Zhou, Changpin; Zhao, Haiwen; Wang, Ping; Li, Fagen (Frontiers in Plant Science, 2023)
Eucalyptus urophylla, E. tereticornis and their hybrids are the most important commercial forest tree species in South China where they are grown for pulpwood and solid wood production. Construction of a fine-scale genetic linkage map and detecting quantitative trait loci (QTL) for economically important traits linked to these end-uses will facilitate identification of the main candidate genes (CGs) and elucidate the regulatory mechanisms. In this regard, a high-density consensus map (a total of 2754 SNPs with 1359.18 cM) was constructed using genotyping by sequencing (GBS) on clonal progenies of E. urophylla × tereticornis hybrids. QTL mapping of growth and wood property traits were conducted in three common garden experiments, resulting in a total of 108 QTLs. Of these, only ten QTLs were found to be stable across two environments, and only one (qStable10 mapped on chromosome 10, and associated with lignin syringyl-to-guaiacyl ratio) was stable across all three environments. Compared to other QTLs, qStable10 explained a very high level of phenotypic variation (18.4–23.6 %), perhaps suggesting that QTLs with strong effects may be more stably inherited across multiple environments. Finally, a total of 1052 CGs were screened by the efficient combination of QTL mapping and transcriptome analysis. The CGs were associated with some transcription factor families, such as TALE, which play an important role in the secondary growth of plant cell walls and the regulation of wood formation. While QTLs such as qStable10, found to be stable across three sites, appear to be comparatively uncommon, their identification is likely to be a key to practical QTL-based breeding. Further research involving clonally-replicated populations, deployed across multiple target planting sites, will be required to further elucidate QTL-by-environment interactions.